2012
DOI: 10.1016/j.biortech.2011.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength specificity of growth, photosynthesis, and hydrocarbon production in the oil-producing green alga Botryococcus braunii

Abstract: The effect of monochromatic light on growth, photosynthesis, and hydrocarbon production was tested in Botryococcus braunii Bot-144 (race B), which produces triterpenoid hydrocarbons. The growth was higher in order of red, blue, and green light. The color of red light-grown cells became more orange-yellow and their shape dominantly changed to grape-like with long branches. Photosynthetic carbon fixation activity was higher in order of blue, red, and green light-grown cells, but photosystem activities showed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 17 publications
1
29
0
2
Order By: Relevance
“…Many recent studies have shown that microalgae grown under monochromatic blue or red light exhibited similar or enhanced growth and productivity rates when compared to that of multi-chromatic white light [1][2][3]36]. By using selective wavelengths of incident light which are complementary or at least close to the maximum absorption of microalgae pigmentation, the use of other wavelengths which are poorly absorbed by the alga is avoided [1,27].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have shown that microalgae grown under monochromatic blue or red light exhibited similar or enhanced growth and productivity rates when compared to that of multi-chromatic white light [1][2][3]36]. By using selective wavelengths of incident light which are complementary or at least close to the maximum absorption of microalgae pigmentation, the use of other wavelengths which are poorly absorbed by the alga is avoided [1,27].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, B. braunii is also a "famous" algal species for its slow growth rate as well as difficult in scaling up (Ruangsomboon, 2012;Baba et al, 2012). Recently, we introduced a novel cultivation system based on biofilm technology, which is called "attached cultivation" .…”
Section: Introductionmentioning
confidence: 99%
“…Baba et al investigated the effect of the light wavelength on the growth and metabolism of Botryococcus braunii Bot‐144 and found that photosynthetic carbon fixation decreased in the order of blue, red, and green light, hydrocarbon production was slightly lower under green light conditions, and red light was optimal for growth. In addition, the results showed that the metabolism of B. braunii Bot‐144 was not influenced by a specific wavelength . The wastewater treatment process is also influenced by light wavelength.…”
Section: Light Characteristics In Microalgae Cultivationmentioning
confidence: 91%